Habituation of Clean and Healthy Living Behavior in Developing Children's Life Skills at Paud Pahlawan - Mediyana, Mediyana; Rifatul Hasanah; Dewi Pusparini (STIT Attaqwa, 2025)
This study aims to describe the implementation of Clean and Healthy Living Behavior (PHBS) in developing early childhood life skills at PAUD Pahlawan, Panaan Village, Pamekasan Regency. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The subjects of the study consisted of 10 children in group A aged 4–5 years, with informants from teachers and principals. The results of the study indicate that PHBS habits are implemented in a structured manner through activities such as washing hands, throwing out trash, maintaining personal hygiene, and tidying up learning tools. Teachers play an active role as guides and role models, and use a fun approach to instill these habits. Supporting factors for PHBS habits are adequate facilities and support from the school, while obstacles include limited facilities and lack of support from the home environment. PHBS habits have a positive impact on children's life skills, especially in the aspects of independence, responsibility, and social concern.